EFFECTS OF PHOTOPERIODS ON THE CLONED GtH GENES IN HARD-LIPPED BARB (Osteochilus hasseltii) - Norman Arie Prayogo; Taufik Budi Pramono; Asrul Sahri Siregar; Purnama Sukardi; Masashi Kawaichi (BIOTROPIA, 2019)
Photoperiod is one of the factors that regulate endocrine gland hormone production necessary for gonadal growth and development, gametogenesis, and reproductive cycles in fish. However, studies on the influence of photoperiod on tropical fishes are still limited. Therefore, this study investigated the effects of photoperiod on the hard-lipped barb, particularly the gene expression of its cloned gonadotropin hormones I (GtH-I) and II (GtH-II). The experiment was designed using three treatments: 14L:10D (control), 8L:16D (short photoperiod), and 18L:6D (long photoperiod). Four aquariums with nine fish per tank were used as replicates. The fish were maintained under these photoperiod treatments for eight weeks. Pituitary activity was observed by measuring GtH gene expression. The length of cDNA GtH-I was 222 bp, and the cDNA GtH-II was 354 bp. The GtH-I precursor encoded by the cDNA consisted of 67 amino acids, including the mature peptide. The level of GtH gene expression significantly increased as longer photoperiods were applied. The results indicated that photoperiod length affects the reproductive performance of the hard-lipped barb.